PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, DAN KOMPETENSI PADA KINERJA KEUANGAN DI SELURUH LEMBAGA PERKREDITAN DESA KECAMATAN DENPASAR SELATAN - I Gede Agustian Zidan; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2022)
Financial performance is one of the measurement tools that users of financial statements use to measure or determine the quality of the business. The population is 161 people and Sampel from this data is 40 respondents were obtained. The data analysis techniques used analysis regresion, t-test and F-test. Based on the results of the study, it can be observed that: (1) the organizational culture does not have a significant influence on the financial performance of community credit institutions, obtaining the values of the regression coefficient 0.054 and sig 0.796. (2) The work environment has a significant positive influence on the financial performance of community credit institutions, obtaining regression coefficient values of 0.499 and 0.020 sig. (3) Competencehas a significant positive effect on the financial performance of community credit institutions, with regression coefficient values of 0.431 and sig 0.013. The advice researchers can give is that the Village Lending Institution in Denpasar City's South Denpasar District is expected to routinely provide socialization, training and mentoring to further enhance the proficiency of lending institutions for the villages.